Identification and Characterization of an Aeromonas hydrophila Oligopeptidase Gene pepF Negatively Related to Biofilm Formation - Du, Hechao; Pang, Maoda; Dong, Yuhao; Wu, Yafeng; Wang, Nannan; Liu, Jin; Awan, Furqan; Lu, Chengping; Liu, Yongjie (Frontiers in Microbiology, 2016)
Bacterial biofilms are involved in adaptation to complex environments and are responsible for persistent bacterial infections. Biofilm formation is a highly complex process during which multifarious genes work together regularly. In this study, we screened the EZ-Tn5 transposon mutant library to identify genes involved in biofilm formation of Aeromonas hydrophila. A total of 24 biofilm-associated genes were identified, the majority of which encoded proteins related to cell structure, transcription and translation, gene regulation, growth and metabolism. The mutant strain TM90, in which a gene encoding oligopeptidase F (pepF) was disturbed, showed significant upregulation of biofilm formation compared to the parental strain. The TM90 colony phenotype was smaller, more transparent, and splendent. The adhesive ability of TM90 to HEp-2 cells was significantly increased compared with the parental strain. Fifty percent lethal dose (LD50) determinations in zebrafish demonstrated that the enhanced-biofilm mutant TM90 was highly attenuated relative to the wild-type strain. In conclusion, the pepF gene is demonstrated for the first time to be a negative factor for biofilm formation and is involved in A. hydrophila pathogenicity.